Saccadic movements using eye-tracking technology in individuals with autism spectrum disorders: pilot study Movimentos sacádicos de indivíduos do espectro autista por varredura visual: estudo piloto - Marcos T. Mercadante; Elizeu C. Macedo; Patrícia M. Baptista; Cristiane S. Paula; José S. Schwartzman (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To verify differences in the visual scanning strategies between pervasive developmental disorders (PDD) and controls when they are observing social and non-social pictures. METHOD: PDD group (PDDG) comprised by 10 non-retarded subjects (age from 4 to 41) and age-matched control group (CG). Nine social pictures with human beings (including two pictures of cat mask), and 3 nonsocial pictures of objects were presented for 5 seconds. Saccadic movements and fixation were recorded with equipment EyeGaze® (LC Technologies Inc.). RESULTS: PDDG (mean=292.73, SE=67.62) presented longer duration of saccadic movements for social pictures compared to CG (mean=136.06, SE=14.01) (p=0.04). The CG showed a higher number of fixations in the picture 7 (a women using a cat mask, with the eyes erased) (CG: mean=3.40; PDDG: mean=1.80; p=0.007). CONCLUSION: The results suggest differences in strategies that PDD explore human picture. Moreover, these strategies seem not to be affected by the lack of expected part of the face (the eyes). OBJETIVO: Verificar diferenças nas estratégias de varredura visual de indivíduos com transtorno invasivo do desenvolvimento (TID) comparados a controles normais na observação de figuras sociais e não sociais. MÉTODO: Estudo caso-controle. Grupo TID: dez sujeitos com TID, inteligência normal e idade entre 4 e 41 anos; Grupo Controle: dez sujeitos pareados por idade. Os sujeitos observaram por 5 segundos 9 figuras de seres humanos e 3 figuras de objetos. Os movimentos sacádicos e o número de fixações foram gravados em equipamento EyeGaze® (LC Technologies Inc.). RESULTADOS: O grupo TID apresentou maior duração dos movimentos sacádicos na observação de figuras humanas [TID=292,73 (EP=67,62); controle= 136,06 (EP=14,01); p=0,04]. O grupo controle apresentou maior número de fixações na figura 7 (mulher com máscara de gato sem os olhos) (TID=1,8; controle=3,4; p=0,007). CONCLUSÃO: Indivíduos com TID parecem utilizar estratégias diferentes para explorar figura humana. Além disso, o padrão de investigação deles não se modifica quando observam uma figura que rompe com o esperado (a falta dos olhos).